Displacement Effect on Local Traders by Emerging Markets: Durban Townships - Dlamin, Machawe Victor; Mbhele, Thokozani Patmond (Journal of Reviews on Global Economics, 2019)
The propounded omnipresent of township malls and aggressive suppliers' expansion into the emerging markets epitomises the greater potential to create jobs and improve the economic transformation. However, it is important to note that these developments could trammel local traders' economic prosperity than abrupt veracity of growth and symbiotic trajectory. While the encroachment of mainstream retailers into South African township markets offers business opportunities and economies of scope to consumers. The objectives which underpinned this study: to explore local township traders' perceptions on the displacement effects from shared value-creation in emerging markets; and to establish the extent of the transformation of retail enterprise development and the displacement of local traders. The study used quantitative methods to analyse the data collected from 301 respondents to amass primary data. The study found that, while local traders appreciate the transformation and development of the townships brought about by shopping mall development, their businesses have been displaced by the emergence of township malls.